#Nazarpemilu: promoting faith-based populist political communication in the Indonesian presidential election 2024 - Nur A. Dwi Putri; Budi Setiyono; Teguh Yuwono; Dewi Erowati (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
We promise to our God the victory of the presidential candidate we support, that is the essence of #nazarpemilu. Promoting of populist political communication that occurred on the social media platform X during the 2024 Indonesian presidential election campaign. The hashtag is a fascinating trend as it combines elements of religion and the election, and it did not originate from the elites but rather from the supporters.Using a content analysis approach this study aims to explore the role of #Nazarpemilu in shaping faith-based populist political communication during the 2024 Indonesian presidential election campaign on the social media platform X.. We found first, #Nazarpemilu contains various hopes and promises from supporters to their God for the victory of the presidential candidate they support. Second, the involvement of some political actors in the hashtag affiliated with parties with Islamic ideologies. Third, some identified messages contain strategies to persuade other users to vote for the supported presidential candidate and strategies to push the movement into the offline realm. Fourth, this hashtag has an exposure effect on other users. Fifth, this hashtag is also tainted by the activities of pro-Prabowo-Gibran candidate pair buzzer activities countering the hashtag with a reversed narrative. Base on this findings that populist content shared by users that appeals to faith-based in the form of hashtags can play an effective role in spreading populist political communication on the social media platform X and have implications for voters mobilization.